The use of microbial rhodopsin proteins in differential photodetection - Reissig, Louisa; Buchanan, Kirstin; Lindner, Thea; Kurihara, Marie; Chan, Po-Chuan; Kibowski, Falk; Kojima, Keiichi; Dalgleish, Simon; Awaga, Kunio; Sudo, Yuki (Frontiers in Physics, 2024)
Transferring information using light signals, and detecting these signals, is not only a cornerstone of modern technology, but has been essential for organisms since evolution provided them with proteins - the cell’s custom-built tools - capable of light to energy conversion or photo-sensing. In this study, the use of diverse representatives of the photoactive protein family of microbial rhodopsins as the active material in differential photodetector devices has been investigated. By modifying the internal parameters of the detectors, such as rhodopsin kind, salinity and pH, as well as by tuning the external environment, such as temperature, we could increase the responsivity and speed of our devices by over 2 orders of magnitude, compared to a previously reported proof-of-concept device, to the µA/W and kHz range, respectively. The characteristic differential photodetector transient signal shape could be stably observed for temperatures up to 70°C and related to features in the protein’s cyclic reaction upon light activation, with the changes in photocurrent shape and polarity concomitantly providing information about the protein used in the device. Furthermore, this study demonstrates that the use of proteins - the cell’s molecular machines - instead of simple organic semiconductor materials can add secondary sensor functionalities to the device if the stimulus (here through temperature and pH) has sufficient effect on the photocurrent signal to allow calibration.